Liposomal delivery of 5 fluorouracil and tretinoin: an aspect of topical treatment of skin warts - Ruchi Tiwari; Gaurav Tiwari; Ankita Wal; Chitranshu Gupta (Facultad de Farmacia, Universidad de Granada, 2020)
ABSTRACT Background: Tretinoin and 5-fluorouracil are indicated for treatment of various skin disorders and actinic keratosis respectively. Objective: Present study was focused to design liposomes containing 5- fluorouracil and tretinoin. Design was further optimized by 32 full factorial design. Methods: Liposomes were prepared by ethanol injection method and evaluated by Transmission Electron Microscopy, percentage entrapment efficiency, zeta potential and in vitro drug release. Optimized formulation was subjected to histopathological and stability studies at 4ºC, 25ºC and 60ºC temperatures. Results: No drug crystals were visible in transmission electron microscopy, regardless of the preparation technique or the loaded drug. Formulation F9 showed maximum drug entrapment of 72.86% and 69.70% for 5-fluorouraciland tretinoin respectively. When phospholipid concentration was increased from 40 to 60 mg/ml, encapsulation efficiencies of formulation increased. Zeta potential and particle size were maintained within range of -19.14 to -25.61 and 100 to 200 nm respectively which facilitated good stability and penetration of liposomes. Dissolution profiles of formulations F1 to F6 showed high amount of drug release (30.6 to 67.42%) at 2 h. Liposomes were not stable at high temperature but formulations were most stable when stored at lower temperature i.e. 4oC. Conclusion: So, in liposomes both 5-fluorouracil and tretinoin were successfully incorporated and it can be further used for formulation development.